2017
DOI: 10.1007/s11605-017-3550-7
|View full text |Cite
|
Sign up to set email alerts
|

Defining Long-Term Survivors Following Resection of Intrahepatic Cholangiocarcinoma

Abstract: While ICC is generally associated with a poor prognosis, some patients will be LT. In fact, even a subset of patients with traditional adverse prognostic factors survived long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…21 The clinical outcomes of patients following liver resection for ICC are, however, highly variable. [22][23][24] The AJCC/UICC staging manual andto a lesser extentthe LCSGJ staging system are generally the most commonly utilized means to stratify patients following surgery for ICC. 9,25 Interestingly, both staging systems are relatively new, having been introduced only 20 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…21 The clinical outcomes of patients following liver resection for ICC are, however, highly variable. [22][23][24] The AJCC/UICC staging manual andto a lesser extentthe LCSGJ staging system are generally the most commonly utilized means to stratify patients following surgery for ICC. 9,25 Interestingly, both staging systems are relatively new, having been introduced only 20 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that the incidence rate of ICC, a rare form of liver cancer, has been rising globally over the past twenty years, which may reflect both a true increase and more accurate diagnosis of the disease (Massarweh & El-Serag 2017;Zhang et al 2016). Additionally, ICC is still a poorly understood malignancy that is strongly characterized by its poor prognosis (Bagante et al 2017;Beal et al 2018). Although scholars have revealed that some conventional medical interventions, such as adjuvant chemotherapy, antiviral therapy, and anatomical resection, might improve the prognosis of ICC patients to some extent, the 5-year OS rate is still only 40% (Lei et al 2018;Schweitzer et al 2017;Si et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, CCA cure is rare, with a 5-year survival ranging from 5% in intrahepatic CCA(iCCA) to 17% in extrahepatic CCA (Squadroni et al, 2017). Factors associated with survival rate of CCA after surgery include tumor size, number of tumors, lymph node metastasis, perineural invasion (PNI), lympho-vascular invasion (LVI) and marginal status (Yamamoto and Ariizumi, 2011;Song et al, 2013;Hartog et al, 2016;Bagante et al, 2017;Jeong et al, 2017;Squadroni et al, 2017;Wellner et al, 2017). However, most of these studies were done in developed countries where the natural history of CCA and its treatment may differ from those in developing countries where there are other causative factors, such as infection with the liver fluke, Opisthorchis viverrini.…”
Section: Survival Of Patients With Cholangiocarcinoma Receiving Surgimentioning
confidence: 99%